Recursos didácticos motivacionales y su relación con el proceso enseñanza-aprendizaje de la lectoescritura para los estudiantes de 3ero “A” del CEB “Dr. Nicanor Larrea León” en el año lectivo 2015-2016. - Moreno Guzmán, Patricia Anabel (2016)
The present project was performed in CEB “Dr. Nicanor Larrea Leon” school, due to the necessity of improving the learning process literacy in children of third “A” of the aforementioned Institution. This research was qualitative and social type, establishes a non-experimental design because were established correlations between the variables of study. The type of research is descriptive, and analyzes a real problem, with a level of exploratory diagnostics because the fundamentals aspects were explored, which were considered in the operationalization of the variable. The population is thirty six (36) students of third grade “A”, the technique for this investigation is primarily done through observation, since this is the best way of learning how the students performed with the application of motivational didactic resources. Once all the data is collected an analysis and interpretation is done where it is determined which motivational literacy process is better for the students. In conclusion, motivational resource education facilitates the learning process of the students and allowed them to learn in a playful and significant way